2016
DOI: 10.1002/chem.201605073
|View full text |Cite
|
Sign up to set email alerts
|

A Redox‐Switchable Germylene and its Ligating Properties in Selected Transition Metal Complexes

Abstract: The synthesis, structure, and full characterization of a redox-switchable germylene based on a [3]ferrocenophane ligand arrangement, [Fc(NMes) Ge] (4), is presented. The mesityl (Mes)-substituted title compound is readily available from Fc(NHMes) (2) and Ge{N(SiMe ) } , or from the dilithiated, highly air- and moisture-sensitive compound Fc(NLiMes) ⋅3 Et O (3) and GeCl . Cyclic voltammetry studies are provided for 4, confirming the above-mentioned view of a redox-switchable germylene metalloligand. Although se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 190 publications
1
34
0
3
Order By: Relevance
“…These compounds of the type [{Fe(η 5 ‐C 5 H 4 ‐N R ) 2 }Ge] ( 1R Ge, R = SiMe 3 , CH 2 t Bu, t Bu, Mes) constitute the first N‐heterocyclic tetrylenes bearing redox‐active substituents . The mesityl homologue 1Mes Ge was studied independently also by Breher and co‐workers . In this context we note that the only ferrocene‐derived germylene with dicoordinate Ge II known to date is Fc* 2 Ge [Fc* = 2,5‐bis(3,5‐di‐ tert ‐butylphenyl)‐1‐ferrocenyl], which was published very recently by Sasamori .…”
Section: Introductionmentioning
confidence: 69%
“…These compounds of the type [{Fe(η 5 ‐C 5 H 4 ‐N R ) 2 }Ge] ( 1R Ge, R = SiMe 3 , CH 2 t Bu, t Bu, Mes) constitute the first N‐heterocyclic tetrylenes bearing redox‐active substituents . The mesityl homologue 1Mes Ge was studied independently also by Breher and co‐workers . In this context we note that the only ferrocene‐derived germylene with dicoordinate Ge II known to date is Fc* 2 Ge [Fc* = 2,5‐bis(3,5‐di‐ tert ‐butylphenyl)‐1‐ferrocenyl], which was published very recently by Sasamori .…”
Section: Introductionmentioning
confidence: 69%
“…Yield: 0. 17 [(LGe)μ-{Mn(CO) 4 }] 2 (7). A solution of 1 (0.39 g, 0.49 mmol) in toluene (12 mL) was added dropwise to a stirred suspension of Mn 2 (CO) 10 (0.20 g, 0.51 mmol) in toluene (12 mL) at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[5] We herein report N-heterocyclic plumbylenes of the type [Fe{(h 5 -C 5 H 4 )NR} 2 PbD]( 1Pb), the heavy analogues of our stable NHCs with a1 ,1'-ferrocenediyl (fc) backbone,w hose ambiphilicity allowed for smallmolecule activation reactions unprecedented for diaminocarbenes. [7] This study revealed that SiMe 3 substituents at the Na toms are suitable to establish reversible redox-chemical behaviour of such NHTs,w hich is why we aimed at the synthesis of [Fe{(h 5 -C 5 H 4 )NSiMe 3 } 2 PbD]( 1aPb). [7] This study revealed that SiMe 3 substituents at the Na toms are suitable to establish reversible redox-chemical behaviour of such NHTs,w hich is why we aimed at the synthesis of [Fe{(h 5 -C 5 H 4 )NSiMe 3 } 2 PbD]( 1aPb).…”
Section: N-heterocyclic Tetrylenes (Nhts) Are Stronger P-acceptorsmentioning
confidence: 99%